Tracing genetic resurrection of pointing dog breeds: Cesky Fousek as both survivor and rescuer - Neradilová, Silvie (PLoS One, 2019)
Cesky Fousek is considered to be one of the oldest pointing dog breeds in Europe and has been appreciated for its versatile working skills. Because it faced extinction in the past, the Cesky Fousek was restored from German Wirehaired and Shorthaired Pointers. Additionally, the breed was recently used in the USA with the initial intent of improvement of the Wirehaired Pointing Griffon (synonymous with Korthals Griffon) by the Bohemian Wirehaired Pointing Griffon Club of America. This study evaluates genetic diversity parameters of Cesky Fousek and compares them to the other continental pointing dogs that played a role in the formation of its gene pool. DNA from buccal swab and blood samples (n = 405) were analyzed using 18 microsatellite markers. Parameters of genetic polymorphism show that the Cesky Fousek breed has a comparable rate of variation as other hunting breeds despite the low population size and severe historical bottlenecks. Clustering analyses reveal a unique genetic status as a distinct pointing dog breed and the relatedness of the breeds is in good concordance with historical data. The present study demonstrates that despite historical admixture among lineages, separate pointing breeds constitute genetically differentiated units, mirroring unique breeding stocks and pedigree isolation among specific breed clubs, reflecting differences in breeding programs under each association.